2015
DOI: 10.17116/oftalma2015131474-78
|View full text |Cite
|
Sign up to set email alerts
|

Chemical microanalysis of mineral deposits on explanted hydrophilic acrylic intraocular lenses

Abstract: The two samples represent two stages of a single process. The early stage is associated with newly formed HA crystals that are unable to cause any significant changes to the lens surface. However, as spherocrystals grow, they exert a crystallization effort that moves their growth centers apart with subsequent lens rupture and deformation. Crystal morphology undergoes dynamic changes: while primary (newly formed) crystals are sheaf-like, mature are spheres. A growing HA is non-stoichiometric. Zinc abundance acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Opacification of hydrophilic IOLs with hydrophobic coating was first described in 2012, and several case reports have been published since then. [10][11][12][13][14] In this cohort, we evaluated 154 eyes implanted with LS-502-1 and found an opacification prevalence of 53.3% (n = 90). To the best of our knowledge, this is not only the largest case series of opacified hydrophilic/hydrophobic IOLs, but also the highest opacification rate ever described for any type of IOL.…”
Section: Discussionmentioning
confidence: 99%
“…Opacification of hydrophilic IOLs with hydrophobic coating was first described in 2012, and several case reports have been published since then. [10][11][12][13][14] In this cohort, we evaluated 154 eyes implanted with LS-502-1 and found an opacification prevalence of 53.3% (n = 90). To the best of our knowledge, this is not only the largest case series of opacified hydrophilic/hydrophobic IOLs, but also the highest opacification rate ever described for any type of IOL.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification of intraocular lenses is a dynamic process. 31 Previously, studies suggested that early stages of newly formed crystals are unable to cause any significant changes to the lens surface, whereas later stages of crystallization can lead to subsequent lens rupture and deformation. 31 Lin et al found mainly poorly-formed crystalline, immature non-stoichiometric deposits in an opacified Hydroview H60 M IOL (Bausch & Lomb, Clearwater, USA) that was in the eye for two years.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Previously, studies suggested that early stages of newly formed crystals are unable to cause any significant changes to the lens surface, whereas later stages of crystallization can lead to subsequent lens rupture and deformation. 31 Lin et al found mainly poorly-formed crystalline, immature non-stoichiometric deposits in an opacified Hydroview H60 M IOL (Bausch & Lomb, Clearwater, USA) that was in the eye for two years. 32 Avetisov et al proposed that calcifications mainly consist of Tricalcium Phosphate [ ] with Zinc impurities possibly playing a role in the calcification process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But capsular biocompatibility of hydrophilic acrylic IOL is low. Capsular biocompatibility is very important because it effects long term visual outcomes negatively through posterior capsular opacification (PCO) and deformation of IOL surface [6] . For this reason, the most of the cataract surgeons use more common hydrophobic acrylic IOL than hydrophilic acrylic IOL if possible.…”
Section: Image Qualitymentioning
confidence: 99%